Analgesic use and associated adverse events in patients with chronic kidney disease: a systematic review and meta-analysis. (March 2022) - Lambourg, Emilie; Colvin, Lesley; Guthrie, Greg; Walker, Heather; Bell, Samira
Abstract: Background: Treating pain in the context of chronic kidney disease (CKD) is challenging because of altered pharmacokinetics and pharmacodynamics, with an increased risk of toxicity and drug adverse events in this population. The aims of this systematic review and meta-analysis were to assess the prevalence of analgesic use and establish the risk of analgesics-related adverse events, in patients with CKD. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Medline, Embase, CINAHL, and CENTRAL were searched until January 2021. Random-effects meta-analyses and meta-regression were conducted to pool and summarise prevalence data and measures of association between analgesic use and adverse events. Results: Sixty-two studies relevant to the prevalence of analgesic use and 33 to analgesic-related adverse events were included, combining data on 2.3 and 3 million individuals, respectively. Pooled analyses found that 41% (95% confidence interval [CI], 35–48) of the CKD population regularly use analgesia. The annual period prevalence was estimated at 50% for opioids and 21% for nonsteroidal anti-inflammatory drugs (NSAID). Overall, 20% and 7% of patients with CKD are on chronic opioid or NSAID therapy, respectively. Opioid use was associated with an increased risk of death (1.61; 95% CI, 1.12–2.31; n = 7, I 2 = 91%), hospitalisation (1.38; 95% CI, 1.32–1.45; n =2, I 2 =0%), and fractures (1.51; 95% CI, 1.16–1.96; n =3, I 2 =54%). Conclusion: High levels of analgesic consumption and related serious adverse outcomes were found in patients with CKD. Consideration needs to be given to how these patients are assessed and managed in order to minimise harms and improve outcomes. Clinical trial registration: CRD42019156491 (PROSPERO).